A comparative study of consistency between Paeonia rubra hort traditional decoction and dispensing granule decoctions from different sources. (2nd December 2022) - Ma, Lijie; Zhang, Huijie; Xu, Manwen; Feng, Wenhao; Shi, Junhan; Wang, Yanli; Zhang, Lu; Gui, Xinjing; Wang, Qingxiao; Wang, Haibo; Yao, Jing; Liu, Ruixin
Abstract: Objective: To compare the consistency between the decoction of Paeonia rubra hort dispensing granules from different manufacturers and traditional decoction (TD), and to provide a reference for the clinical application of Paeonia rubra hort dispensing granules. Methods: Nine batches of Paeonia rubra hort dispensing granules (from three manufacturers, A, B, and C) and 20 batches of Paeonia rubra hort decoction pieces were collected. The contents of four active components in vivo and in vitro were determined by HPLC and UPLC-MS/MS, respectively. The consistency of the Paeonia rubra hort decoction pieces and dispensing granules were compared based on the Criteria Importance Though Intercrieria Correlation (CRITIC) weighting method and the equivalent correction suggestions (1 g of dispensing granule equals the same amount of Chinese herbal samples) were put forward for the dispensing granules. Results: The total content of active ingredients in vivo and in vitro of manufacturer A was significantly lower than that of TD ( p < 0.05), and the total content of active ingredients in vivo of manufacturer C was significantly lower than that of TD ( p < 0.05); The equivalent of manufacturer A and manufacturer C should be corrected from 1:11 and 1:5 to 1:5 and 1:4, respectively. Conclusion: The quality of Paeonia rubra hort dispensing granule decoction from some manufacturers aligns that of TD, but the other is slightly inferior to that of TD. After appropriate equivalent correction, quality consistency can be achieved with TD. Graphical Abstract: UF0001